2022
DOI: 10.1097/01.reo.0000000000000318
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Nutrition-Related Beliefs, Behaviors, and Challenges in Individuals Living With Cancer and Their Caregivers

Abstract: Background and Purpose: This study explored physical activity and nutrition beliefs, behaviors, and challenges; examined dyadic interactions; and explored lifestyle programming preferences to inform future interventions to improve the physical and mental health of patients with cancer and their caregivers. Methods: A convergent mixed-methods design with structured surveys and interviews. Descriptive statistics and quantitative comparisons were performed using SAS. Interviews were analyzed using inductive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
(149 reference statements)
0
5
0
Order By: Relevance
“…Studies have found that receiving guidance and clear recommendations from trusted sources, such as healthcare providers, positively influences cancer survivors' motivation to change their nutrition behavior. [50][51][52] For example, a qualitative study in the UK by Beeken et al among adult cancer survivors exploring their beliefs about dietary quality and cancer found participants to be skeptical about nutrition information from sources other than healthcare providers. 51 Similarly, in another study that investigated the influence of nutritional information on dietary behaviors among Dutch cancer survivors, respondents indicated that they preferred to receive nutrition information from healthcare professionals (oncology nurses, registered dietitians, and doctors).…”
Section: Facilitators Of Healthful Nutritionmentioning
confidence: 99%
“…Studies have found that receiving guidance and clear recommendations from trusted sources, such as healthcare providers, positively influences cancer survivors' motivation to change their nutrition behavior. [50][51][52] For example, a qualitative study in the UK by Beeken et al among adult cancer survivors exploring their beliefs about dietary quality and cancer found participants to be skeptical about nutrition information from sources other than healthcare providers. 51 Similarly, in another study that investigated the influence of nutritional information on dietary behaviors among Dutch cancer survivors, respondents indicated that they preferred to receive nutrition information from healthcare professionals (oncology nurses, registered dietitians, and doctors).…”
Section: Facilitators Of Healthful Nutritionmentioning
confidence: 99%
“…Several studies have reported caregivers as a primary influence of patient dietary change. 16,[48][49][50] For example, in a study among patients with colorectal cancer and their caregivers, Lee et al found that patients were more likely to adopt healthful diets if their caregivers prioritized improving their own diets. 50 Similarly, in two qualitative investigations of barriers and facilitators of dietary change after prostate cancer diagnosis, Kassianos et al and Avery et al found that participants' wives and partners played central roles in food choice and preparation.…”
Section: Influential Othersmentioning
confidence: 99%
“…13,14 In addition to poor prognosis, caregivers report that patient weight loss, malnutrition, and further deterioration of patients’ nutrition status are major sources of distress, negatively impacting their own emotional and physical wellbeing. 8,15,16…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations